Diabetes and cognitive deficits in chronic schizophrenia: a case-control study. - Mei Han; Xu-Feng Huang; Da Chun Chen; Meihong Xiu; Thomas R Kosten; Xiang Yang Zhang (PLoS ONE)
Cognitive impairment occurs in both schizophrenia and diabetes. There is currently limited understanding whether schizophrenia with diabetes has more serious cognitive deficits than schizophrenia without diabetes or diabetes only. This study assessed cognitive performance in 190 healthy controls, 106 diabetes only, 127 schizophrenia without diabetes and 55 schizophrenia with diabetes. This study was conducted from January 2008 to December 2010. Compared to healthy controls, all patient groups had significantly decreased total and five index RBANS scores (all p<0.01-p<0.001), except for the visuospatial/constructional index. Schizophrenia with diabetes performed worse than schizophrenia without diabetes in immediate memory (p<0.01) and total RBANS scores (<0.05), and showed a trend for decreased attention (p = 0.052) and visuospatial/constructional capacity (p = 0.063). Schizophrenia with diabetes performed worse than diabetes only in immediate memory (p<0.001) and attention (p<0.05), and showed a trend for decreased total RBANS scores (p = 0.069). Regression analysis showed that the RBANS had modest correlations with schizophrenia' PANSS scores, their duration of current antipsychotic treatment, and diagnosis of diabetes. Schizophrenia with co-morbid diabetes showed more cognitive impairment than schizophrenia without diabetes and diabetes only, especially in immediate memory and attention.